Quantitative proteomics defines mechanisms of antiviral defence and cell death during modified vaccinia Ankara infection - Jonas D. Albarnaz; Joanne Kite; Marisa Oliveira; Hanqi Li; Ying Di; Maria H. Christensen; Joao A. Paulo; Robin Antrobus; Steven P. Gygi; Florian I. Schmidt; Edward L. Huttlin; Geoffrey L. Smith; et al. (Nature Communications, 2023)
Abstract Modified vaccinia Ankara (MVA) virus does not replicate in human cells and is the vaccine deployed to curb the current outbreak of mpox. Here, we conduct a multiplexed proteomic analysis to quantify >9000 cellular and ~80% of viral proteins throughout MVA infection of human fibroblasts and macrophages. >690 human proteins are down-regulated >2-fold by MVA, revealing a substantial remodelling of the host proteome. >25% of these MVA targets are not shared with replication-competent vaccinia. Viral intermediate/late gene expression is necessary for MVA antagonism of innate immunity, and suppression of interferon effectors such as ISG20 potentiates virus gene expression. Proteomic changes specific to infection of macrophages indicate modulation of the inflammatory response, including inflammasome activation. Our approach thus provides a global view of the impact of MVA on the human proteome and identifies mechanisms that may underpin its abortive infection. These discoveries will prove vital to design future generations of vaccines.